Changing Winter Landscapes: Extreme Weather Events and Meanings of Snow for Sámi Reindeer Herders - Markkula, Inkeri; Turunen, Minna; Rasmus, Sirpa; Rikkonen, Taru; Koski, Veina; Welker, Jeffrey M. (The Arctic Institute of North America, 2025)
Snow is a crucial part in the lives of Sámi reindeer herders, and changes in snow conditions can affect their well-being in multiple ways. However, meanings and emotions associated with snow are rarely considered in research on reindeer herding and climate change. Based on thematic interviews with reindeer herders in two reindeer herding co-operatives in the Sámi Homeland in Finland, we examined the roles and meanings of snow for Sámi reindeer herders and impacts of the extreme winter events of recent years on their well-being. In addition, based on a literature survey, we considered the role of reindeer herders’ snow knowledge in climate change research related to the Sámi area in Finland, Sweden, and Norway. Our results show that snow plays multiple roles in the lives of reindeer herders. The extreme snow conditions of recent years have had a significant negative impact on reindeer herder well-being, and at the same time, snow is connected to happiness, sense of place, and cultural continuity. The embeddedness of snow with different kinds of cultural and intrinsic meanings should receive more attention in research on the impacts of climate change on the lives of Sámi and other Arctic peoples. In the literature we analyzed, the snow knowledge of Sámi reindeer herders was constructed in multiple ways. This practical knowledge system informing, as it does, daily activities and assessments of the future, is not only crucial for reindeer herders themselves, but also for society at large, as it can enhance education and bring important insights into climate change research and adaptation. La neige joue un rôle important dans la vie des Sámis éleveurs de rennes. Les changements caractérisant l’état de la neige peuvent donc avoir des incidences sur leur bien-être de plus d’une manière. Cependant, il arrive rarement que les recherches sur l’élevage des rennes et le changement climatique tiennent compte des significations de la neige et des émotions qui s’y rattachent. À partir d’entretiens thématiques avec des ...